In vitro pathological modelling using patient-specific induced pluripotent stem cells: the case of progeria. (21st November 2011) - Nissan, Xavier; Blondel, Sophie; Peschanski, Marc
Abstract : Progeria, also known as HGPS (Hutchinson–Gilford progeria syndrome), is a rare fatal genetic disease characterized by an appearance of accelerated aging in children. This syndrome is typically caused by mutations in codon 608 (C1804T) of the gene encoding lamins A and C, LMNA, leading to the production of a truncated form of the protein called progerin. Owing to their unique potential to self-renew and to differentiate into any cell types of the organism, pluripotent stem cells offer a unique tool to study molecular and cellular mechanisms related to this global and systemic disease. Recent studies have exploited this potential by generating human induced pluripotent stem cells from HGPS patients' fibroblasts displaying several phenotypic defects characteristic of HGPS such as nuclear abnormalities, progerin expression, altered DNA-repair mechanisms and premature senescence. Altogether, these findings provide new insights on the use of pluripotent stem cells for pathological modelling and may open original therapeutic perspectives for diseases that lack pre-clinical in vitro human models, such as HGPS.